Situational Constraints and Work Outcomes: The Influences Of a Frequently Overlooked Construct - Peters, Lawrence H.; O’Connor, Edward J. (Academy of Management Review, 1980)
We present a conceptual framework specifying the hypothesized influences of situational constraints on work outcomes and individual difference to work outcome associations. In addition to reviewing the relevant literature and discussing the implications for researchers and practitioners, we suggest a systematic program of needed research.